Extraction of raw cellular wall of Enterobacter cloacae and study of its toxicity - N. Sh. M. Hussain; M. T. flaih (مجلة بغداد للعلوم)
The crude cell wall of E.cloacae was extracted by using Lysozyme , DNase and RNase enzymes, the contents of the proteins and carbohydrates were 24% and 1.44% respectively .